Pediatric Rheumatology Collaborative Study Group - over four decades of pivotal clinical drug research in pediatric rheumatology - Hermine I. Brunner; Lisa G. Rider; Daniel J. Kingsbury; Dominic Co; Rayfel Schneider; Ellen Goldmuntz; Karen B. Onel; Edward H. Giannini; Daniel J. Lovell; for the PRCSG Advisory Council (BMC, 2018)
Abstract Importance Specialized research networks are essential to achieve drug approvals for rare pediatric diseases. Such networks help realize the potential of global legislation enacted upon the recognition that most children are treated with drugs whose most beneficial dose and regimen have not been established in pediatric patients. The Pediatric Rheumatology Collaborative Study Group (PRCSG) is a North American clinical trials network that is specialized in the performance of clinical trials of new therapies for pediatric populations with rheumatic diseases. This review provides an overview of the strategies employed by this research network to achieve drug and biologic approvals for children with pediatric rheumatic diseases, particularly juvenile idiopathic arthritis. Observations Clinical trial conduct in rare pediatric diseases has required global recruitment. Supported or led by the PRCSG, highly responsive, validated, composite measures have been established to assess drug efficacy. For pediatric orphan diseases with high disease burdens, specialized investigative sites and study designs are needed to complete adequately powered trials at the high standard necessary to enable drug labeling by regulatory agencies. Novel trial designs have been utilized for more efficient testing of innovative drug candidates. All these have been developed or co-developed by the PRCSG research network. Conclusions and relevance Specialized research networks in pediatric rheumatology, such as the PRCSG, have changed the landscape of available therapies and improved overall disease outcomes for children with pediatric rheumatic diseases.